Stock market integration and the ASEAN Trading Link an empirical study - Sulong, Rizal Lynam Matjeraie (2019)
An analysis of the extent of stock market integration of the participants of the ASEAN Trading Link (ATL) through an empirical study of the stock markets of Singapore, Thailand & Malaysia. Examines which of the stock market participants of the ATL became more closely integrated before, during and after the period the ATL was in operation and also considers their relationship with a non-participant stock market of the ATL, Hong Kong, over the same periods. The assessment of market integration in the selected stock markets begins with preliminary tests to evaluate descriptive statistics, correlation and unit root tests of stock returns, after which tests for cointegration are applied including an Engle & Granger test, Granger Causality test and the Johansen test. The findings show that there is progressively less stock market integration for the participants of the ATL from the period in which the link is launched, to the period after it is taken offline, indicating that there are continued potential benefits from diversifying an investment portfolio across the three stock markets. The status of the Singapore stock market as a key influencer in ASEAN is reaffirmed, as well as the existence of traces of historical linkages between the stock markets of Singapore and Malaysia.